Clinical Onset and Multiple Sclerosis Relapse after SARS-CoV-2 Infection - Antonia Pignolo; Maria Aprile; Cesare Gagliardo; Giovanni Maurizio Giammanco; Marco D'Amelio; Paolo Aridon; Giuseppe La Tona; Giuseppe Salemi; Paolo Ragonese (MDPI AG, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been associated with several neurological disorders including headache, facial palsy, encephalitis, stroke, demyelinating disorders. The present report will discuss cases of multiple sclerosis (MS) onset and relapse both beginning early after SARS-CoV-2 infection. In both cases, magnetic resonance imaging (MRI) showed widespread bilateral subcortical and periventricular active lesions. Serum IgG against SARS-CoV-2 Spike antigens confirmed seroconversion with titers that are considered not definitely protective against possible reinfection. We hypothesize that SARS-CoV-2 infection, as previously reported for other viruses, could drive an active inflammatory response that can contribute either to the onset of MS or its relapse. The presented data further support the importance of vaccination in individuals with MS.